What's New: Memoirs of a Socialist Idealist - Hannant, Larry (Labour / Le Travail, 2009)
The article reviews the book, "What's New: Memoirs of a Socialist Idealist," by Ben Swankey.
Keywords: BOOKS – Reviews; Communism; Nonfiction; SWANKEY; Ben; WHAT'S New: Memoirs of a Socialist Idealist (Book)